Prohibition of fur farming in Lithuania: a justified animal protection measure or an excessive restriction of freedom of economic activity? - Saladžius, Adomas; Pikūnas, Ainius (Vilnius University Open Series, 2024)
The research work analyses the jurisprudence of the Constitutional Court, the European Court of Human Rights and the Court of Justice of the European Union and legal doctrine relevant to restrictions on the freedom of economic activity (inter alia, the prohibition of economic activity). Based on these sources, the conditions for the application of the most stringent measure restricting the freedom of economic activity – prohibition of economic activity – are identified. After discussing the theoretical aspect of the prohibition of economic activity, a legal analysis of a practical example – the prohibition of breeding and keeping fur-bearing animals – is presented.In the first parts of the thesis, an analysis of the doctrine of the Constitutional Court and supranational courts reveals the prevailing concept of freedom of economic activity at the national and international levels, as well as the main conditions for its restriction. Furthermore, the key measures for the protection of legitimate expectations in the event of a prohibition of economic activity are identified.The paper then analyses the specific case of the prohibition of breeding and keeping of fur-bearing animals in Lithuania as of 1 January 2027 from the point of view of the conditions set out in the doctrine, the principles of proportionality and the protection of legitimate expectations. Considering that the prohibition of breeding and keeping of fur-bearing animals is the first case of a complete prohibition of economic activities in Lithuania, the authors of this paper analyse the proportionality of the regulation in question and the guarantee of the protection of legitimate expectations, using the examples of vacatio legis and compensation mechanisms provided for in analogous legal regulations adopted abroad. The work also analyses the compliance of the established compensation mechanism for losses incurred by the breeders of fur-bearing animals with the Constitution and the legal principles.
Keywords: freedom of economic activity; prohibition of economic activity; animal rights; environmental protection